PENGARUH GAYA HIDUP HEDONISME, PENGALAMAN KEUANGAN, DAN PENGETAHUAN KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN - Munir Nur Komarudin; Herma Wiharno; Rina Masruroh (ITB AAS Indonesia, 2025)
The aim of this research is to analyze whether there is an influence of Hedonistic Lifestyle, Financial Experience, and Financial Knowledge on Financial Management Behavior. The research method used was quantitative with the population in this study being PKK women in Kuningan Regency, totaling 1,183 people. The sampling method used was proportional simple random sampling, the data collection technique used in this research was through distributing questionnaires and measuring using an interval scale. The research results show that the hedonistic lifestyle has a positive and significant influence on financial management behavior, financial experience has a positive and significant influence on financial management behavior, financial knowledge has a positive and significant influence on financial management behavior and simultaneously all three influence financial management behavior.